Effect of Stacking Sequence on Mechanical and Water Absorption Characteristics of Jute/Banana/Basalt Fabric Aluminium Fibre Laminates With Diamond Microexpanded Mesh - Padmanabhan Rengaiyah Govindarajan; Rajesh Shanmugavel; Karthikeyan Subramanian; Sivasubramanian Palanisamy; Carlo Santulli; Cristiano Fragassa (International Journal of Polymer Science)
This research focuses on hybrid woven fibre metal laminates (HWFMLs), specifically on the innovative hybridization of natural woven fibres (NWFs) with aluminium diamond microexpandable mesh (Al-DMEM) in thin laminates. More specifically, it investigates the effect on the mechanical and water absorption properties of incorporating basalt (B), jute (J), banana (Bn) fibres, and Al-DMEM as reinforcing materials in a traditional epoxy resin. Several stacking sequences were compared and discussed. The basalt-banana-aluminium-banana-basalt (BBnABnB) (five layers) laminate exhibited remarkable compressive strength (25.7 MPa), interlaminar shear strength (25.2 MPa), Izod impact strength (2.98 J), tensile strength (42.8 MPa), and tensile modulus (3.1 GPa). Other laminates, despite their limited tensile strain, still offered advantages in other loading modes. In particular, basalt-jute-aluminium-jute-basalt (BJAJB) (five layers) laminate showed notable performance with a compressive strength of 16.70 MPa and interlaminar shear strength of 20.85 MPa. In comparison, the basalt-aluminium-basalt (BAB) (three layers) demonstrated compressive strength equal to 6.87 MPa and interlaminar shear strength (ILSS) equal to 9.07 MPa.